1968
DOI: 10.1037/h0026483
|View full text |Cite
|
Sign up to set email alerts
|

Some determinants of communication accuracy.

Abstract: Communication accuracy is defined, and various measures of accuracy which have been employed in the research literature are discussed. Considered as the dependent variable, accuracy in communication is conceptualized as being determined by 5 sets of independent variables: attributes of the communicator, of the addressee, of the channel, of the communication, or of the referent. With these as independent variables, a series of hypotheses is suggested for predicting variations in communication accuracy. For each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

1971
1971
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
1
22
1
Order By: Relevance
“…Research in social and cognitive psychology (1,11,15) has indicated that the level of miscomprehension tends to be higher when the message: (a) is more complex, (b) contains a greater amount of information, (c) is more emotionally loaded, (d) is more abstract, (e) is more disjointed in organization, (f) contains distractions (competing stimuli, music, etc.) and (g) is contextbound (the message would have a different meaning in a different context).…”
Section: Factors Underlying Message Miscomprehensionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research in social and cognitive psychology (1,11,15) has indicated that the level of miscomprehension tends to be higher when the message: (a) is more complex, (b) contains a greater amount of information, (c) is more emotionally loaded, (d) is more abstract, (e) is more disjointed in organization, (f) contains distractions (competing stimuli, music, etc.) and (g) is contextbound (the message would have a different meaning in a different context).…”
Section: Factors Underlying Message Miscomprehensionmentioning
confidence: 98%
“…Finally, audience/receiver factors which are specific to each receiver can contribute to message miscomprehension (1,11,15,19). The most important factors are: (a) previous knowledge and beliefsif a consumer's knowledge structures regarding the product and the message are well formed, one would expect miscomprehension to be less.…”
Section: Factors Underlying Message Miscomprehensionmentioning
confidence: 99%
“…The shape is the location of the feature points. If there are h feature points, the shape vector can be represented as (1). The texture is the pixel intensities or colors.…”
Section: Modellingmentioning
confidence: 99%
“…According to Mehrabian's rule [1], in human-human communication, only seven percent of the information that we send is verbal, 38 percent is sent in acoustic signals, such as tone of voice, and 55 percent is sent through visual signals, such as facial expressions and gestures. Therefore, the ability to understand human non-verbal signals is essential.…”
Section: Introductionmentioning
confidence: 99%
“…(FF) (NW) (Martens, 1975) (Ravaja et al, 2006;Cooke et al, 2013) (Krantz & Ratliff-Crain, 1989;Sherwood et al, 1989) (Mayet & Hughes, 2003) (Harrison et al, 2001;Veldhuijzen van Zanten et al, 2002) 2004 (Cooke, Kavussanu, McIntyre, & Ring, 2011;Cooke et al, 2013) (Ravaja et al, 2006;Ricarte et al, 2001) (Lim & Reeves, 2010) (Greenberg et al, 2010;Yee, 2006) 2004 (Mehrabian, 1968) …”
mentioning
confidence: 99%